The Principles Of Contract In Donation Based Crowdfunding - L Budi Kagramanto; Cita Yustisia Serfiyani (Yuridika, 2019)
The creative economy is a new era of the global economy. It needs support from the government and the society in terms of intellectual property rights protection and funding, especially for creative business or creator which comes from small and medium business (SMB) sector. One of the ways other than formal funding from the bank is through the crowdfunding new system. Crowdfunding has four systems that are based on donation, reward, lending, and equity. Donation-based crowdfunding is the most common type applied and different from other crowdfunding types. This field has not been regulated in specific legislation so it needs to be analyzed in relation to BW and related existing regulation. This research is leading to answers some main topics. First, to analyze the legal relationship between the parties. Second, to determine what type of agreement that underlies the legal act. Third, reviewing the principles of contract law that must be applied to. In the article, it uses the type of research used in this research method is normative research so that it produces a legal review of the donation-based crowdfunding system issues more deeply.